If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -3x = 5 Reorder the terms: -3x + 3y = 5 Solving -3x + 3y = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. -3x + 3y + -3y = 5 + -3y Combine like terms: 3y + -3y = 0 -3x + 0 = 5 + -3y -3x = 5 + -3y Divide each side by '-3'. x = -1.666666667 + y Simplifying x = -1.666666667 + y
| -22-3e=-2e+e-3e | | 2(y-3)-2=2 | | 7(x+5)-2x-40=-3(2x-9.4)+4 | | 9(n+6)=10 | | -11+p=-5 | | 0.04y=0.02-y | | 0=y^2-6y | | -.4f+2=.2f+11 | | 6x^3-x^2-5x=0 | | 90=1500*r*2 | | y=41/11(88)+128/11 | | 4x-6=3x+6 | | .25+x=-.58 | | 7(3x+6)=7-(x-2) | | 8(v+2)-4v=2(2v+1)-4 | | y=41/11(20)+128/11 | | -6m-6+8m=-5m-5+2m-1 | | y=41/11(18)+128/11 | | 3=4p+8-3p | | -30=5r | | (y-4)(3-7)=.25 | | 3c+5=2c+2 | | 67x-34+2=5 | | 8(v+2)-4v+7=8v+7 | | 3+(56+x)=34 | | 21j-12=14j+37 | | -6y+14+14y=32 | | 7=-d+13 | | -21.2=p-12.7 | | .333h-4(.666h-3)=.666h-6 | | 8-5n=-7 | | 18a^6-25a^5+8a^4=0 |